Kolaborasi Pentahelix dalam Pengembangan Pariwisata Berkelanjutan di Ibu Kota Nusantara - Dananjaya, Ahmad Ghazy (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2025)
This study aims to analyze the collaboration among stakeholders in the Pentahelix model for the development of sustainable tourism in Indonesia’s new capital city, Ibu Kota Nusantara (IKN). Designed with a green, smart, and inclusive approach, IKN faces challenges in building a tourism sector that not only promotes economic growth but also considers social, cultural, and environmental dimensions. The Pentahelix model—which involves five key elements: government, academia, business, community, and media—is seen as a relevant collaborative framework to encourage synergy in sustainable destination development. This research uses a mixed-method approach by combining quantitative data from 400 respondents with in-depth interviews involving representatives from each Pentahelix element. The quantitative analysis aims to measure public perceptions of the effectiveness and contribution of each actor, while the qualitative analysis explores collaboration practices, existing barriers, and the potential to strengthen cross-sector synergy. The findings indicate that cross-sector collaboration significantly contributes to the formation of IKN’s tourism identity, the preservation of local values, and the application of sustainable innovations. Key challenges include coordination among actors, limited local human resource capacity, and policy integration. This study recommends the establishment of a multi-stakeholder communication forum, enhancement of tourism literacy among local communities, and the use of digital technology and media to support destination branding. With strong Pentahelix collaboration, IKN has the potential to become a model for sustainable urban tourism development in Indonesia’s future cities.